Evaluasi Kinerja Jaringan Daerah Irigasi (D.I) Jeuram Kabupaten Nagan Raya - Hasdanita, Fitry; Dinda, Raina Parmitalia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Evaluation of irrigation systems will become more important in improving the performance of irrigation networks to achieve optimal productivity in the context of increasing food needs and competition for limited water resources. Performance assessment is used to ascertain the current state of schemes relative to benchmarks and helps uncover the underlying reasons for poor performance, thereby suggesting opportunities for improvement. two main approaches to performance evaluation are considered: how well the service is delivered and irrigation outcomes in terms of efficiency and productivity of water resource use. This research aims to obtain the performance of the D.I Jeuram network, understand the problem of water loss, and improvement efforts that will be made to address the problem of rice field water needs. Apart from that, to increase Operation and Maintenance activities at D.I Jeuram. The research method was carried out using a survey and inventory of D.I. Jeuram using direct observation, guided by PUPR Ministerial Decree No. 12/PRT/M/2015. Based on the results of observations and inventory, irrigation performance evaluations were then carried out to assess physical infrastructure, plant productivity, supporting facilities, personnel organization and documentation. The results of D.I Jeram's performance assessment were 59.32% in the poor category and really need attention. This condition affects plant productivity. The cross-section of the primary channel is still able to accommodate water discharge to flow to the rice fields. The condition of the primary channel is in the category of moderate to severe damage, as well as uncontrolled sedimentation. This also affects plant productivity, so it is necessary to repair, operate and maintain irrigation either routinely or periodically.